2017
DOI: 10.1038/s41598-017-01489-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorder, an independent risk associated with arterial stiffness in menopause

Abstract: As women age and go through menopause, they suffer a higher incidence of sleep disorder, cardiovascular morbidity and mortality. In addition, evidences suggested that sleep disorder was an important pathological indicator for coronary heart disease. However, the relationship between different menopausal status, sleep disorder and cardiovascular diseases was unclear. Thus, we aim to assess the association between sleep disorder with arterial stiffness in females of 40–60 years free of cardiovascular diseases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…The demographic information was obtained using a general questionnaire, and it has been applied previously, which was administered by well‐trained investigator through face‐to‐face interview. Hypertension was defined as self‐report of any prior diagnosis or by criteria recommended by the seventh report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC7) .…”
Section: Methodsmentioning
confidence: 99%
“…The demographic information was obtained using a general questionnaire, and it has been applied previously, which was administered by well‐trained investigator through face‐to‐face interview. Hypertension was defined as self‐report of any prior diagnosis or by criteria recommended by the seventh report of the Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC7) .…”
Section: Methodsmentioning
confidence: 99%
“…81 In summary, primary sleep disorders become more prevalent in older age, affecting > 53% of postmenopausal women. [103][104][105] Moreover, poor sleep in perimenopausal/postmenopausal women is associated with inflammation, 106 cardiovascular and metabolic disease, [107][108][109] and mood disorders. Understanding the evolution of sleep across a woman's life span may lead to effective therapies that affect women's health and quality of life.…”
Section: Sleep Changes Related To Mood Disordersmentioning
confidence: 99%
“…OSA is supposed to be more prevalent in men than women, however the gap was narrowed when women approach menopause [6,7]. Women in menopause transition are more likely to report perspective poor sleep, snoring [8], which largely affected quality life of menopausal women. In addition, previous studies have reported that menopause was an important risk factor for snoring mainly due to the declining ovarian hormones [9,10].…”
Section: Introductionmentioning
confidence: 99%